The The Implications of the Clash Between Islamic Worldview and Modernity in the Thought of Syed Muhammad Naquib Al-Attas - Andhara; Wirman Tobing; Ryandi (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Contemporary Muslims face a crisis that is not merely material or technological but strikes at the very foundations of their worldview. This study aims to examine the concept of the Islamic worldview in the thought of Syed Muhammad Naquib al-Attas, identify the forms of its clash with the Western modern worldview, and analyze the implications of that clash for the epistemological and spiritual condition of contemporary Muslims. The research employs a qualitative method based on a biographical study approach with a library research design, utilizing descriptive-analytical-critical content analysis of al-Attas's primary works, chiefly Prolegomena to the Metaphysics of Islam (1995) and Islam and Secularism (1978). The findings reveal that al-Attas's Islamic worldview, which he terms ru'yat al-Islam li al-wujud, is composed of eight fundamental elements centered on God (Allah) and characterized by theocentrism, a vertical-hierarchical order, an integrative nature, and an eschatological orientation. The clash between the Islamic worldview and Western modernity operates simultaneously on four levels: metaphysical, epistemological, anthropological, and axiological. This clash produces at least three major epistemological implications: confusion of knowledge, the dichotomy between religious and secular sciences as a colonial legacy, and an intellectual identity crisis resulting in the rise of leaders lacking an adequate worldview. On the spiritual level, the clash triggers loss of adab as the root of all crisis, spiritual disorientation, and the desacralization of life, reducing religion to formal ritual disconnected from daily living. As a solution, al-Attas proposes the Islamization of knowledge, which operates at the worldview level rather than merely the methodological one. The study concludes that the crisis of the Muslim community stems from the erosion of the Islamic worldview as the foundation of thought, and its restoration is a prerequisite for any sustained civilizational renewal in Islam.